Tirzepatide in Sport: A Comprehensive Review of its Metabolic Impacts and Potential Applications for Athletes - Biesiada, Wiktor; Kopczyńska, Ewelina; Kulej, Piotr; Woźniak, Justyna; Kmieć, Justyna Weronika; Chernysh, Anna-Mariia; Dusińska, Aleksandra; Waszczyński, Jakub; Fuczyło, Kamila; Stankevič, Karolina (Quality in Sport, 2025)
Introduction Tirzepatide, a dual agonist of glucose-dependent insulinotropic peptide (GIP) and glucagon-like peptide-1 (GLP-1) receptors, has emerged as a transformative metabolic therapy with exceptional efficacy in weight management and glycemic control. Its relevance in sports science is growing, with potential benefits in weight optimization, energy balance, and recovery. By influencing glucose homeostasis, fat oxidation, and systemic inflammation, tirzepatide may enhance athletic performance. This review examines its pharmacological effects, impact on body composition, and implications for endurance, strength, and recovery in athletes, while addressing ethical and regulatory considerations, including anti-doping concerns. Purpose of the Work: To analyze tirzepatide’s pharmacological actions, clinical effects, and potential applications in optimizing sports performance, recovery, and body composition. Materials and Methods: A comprehensive review of scientific literature was conducted across databases including PubMed, Scopus, Web of Science, Embase, and Google Scholar. Search terms encompassed tirzepatide, GLP-1/GIP dual agonist, metabolic therapy, sports performance, body composition, endurance, and athlete recovery. Relevant studies were synthesized to compile findings. Results: Tirzepatide provides significant metabolic benefits, such as enhanced fat oxidation, improved glucose regulation, and reduced systemic inflammation. Its effects on body composition include substantial fat mass reduction, particularly visceral adiposity, while preserving lean muscle mass. These attributes suggest its potential to enhance endurance via glycogen-sparing mechanisms and improve recovery after exercise. However, concerns about misuse in competitive sports underline the need for regulatory oversight. Further research is necessary to evaluate tirzepatide’s long-term effects on athletic performance and address associated ethical challenges.